2022
DOI: 10.1108/ijrdm-09-2020-0374
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of showrooming behaviour: insights from integrated perspectives

Abstract: PurposeThe paper investigates shoppers' justification behind the showrooming behaviour and proposes an integrated SOR-MOA framework and a SAP-LAP model for a better understanding of the showrooming phenomenon.Design/methodology/approachThe study adopts a qualitative approach. A narrative-based examination followed by an inductive thematic analysis was employed to discover consumers' reasoning behind showrooming.FindingsThe results of the study affirmed the distinction between situational and intentional showro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 76 publications
(212 reference statements)
0
19
0
Order By: Relevance
“…The managerial implications of this research even extend to offline businesses attempting to curtail showrooming. This study emphasised the use of various variables that may be considered while developing an optimal strategy, like price, store closings (Akturk and Ketzenberg, 2021), the effectiveness of salesperson interactions, situational factors (Arora et al, 2022), the role of technology like AI, AR, VR and customer proximity to retailers (Lim et al, 2022(Lim et al, , 2023a. However, it was also pointed out that companies may use "loyal showrooming" to their advantage in order to retain customers.…”
Section: Discussionmentioning
confidence: 99%
“…The managerial implications of this research even extend to offline businesses attempting to curtail showrooming. This study emphasised the use of various variables that may be considered while developing an optimal strategy, like price, store closings (Akturk and Ketzenberg, 2021), the effectiveness of salesperson interactions, situational factors (Arora et al, 2022), the role of technology like AI, AR, VR and customer proximity to retailers (Lim et al, 2022(Lim et al, , 2023a. However, it was also pointed out that companies may use "loyal showrooming" to their advantage in order to retain customers.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making style was found to influence multichannel shopping behavior (Harris et al, 2021), while the role of pricing in combating showrooming behavior was examined in another (Chai et al, 2021). Other studies examined the drivers of showrooming behavior (Arora et al, 2022), including the influence of product attributes (Guo et al, 2021), online engagement (Shankar, Yadav, et al, 2021), and mobile dependency (Chimborazo-Azogue et al, 2022). Location-based retail apps and their effect on perceived value and consumer response were also investigated (Kim, 2021).…”
Section: Pandemic Studies (Ts3 Period)mentioning
confidence: 99%
“…Hence, consumers seeking the lowest price for their desired product are more inclined to engage in showrooming, whereas those prioritizing convenience and product verification tend to adopt webrooming (Aw et al, 2021;Chung et al, 2021). Alongside the prevalence of showrooming and webrooming, scholars have explored their drivers from an economic perspective (Arora et al, 2021(Arora et al, , 2022Aw, 2019;Chimborazo-Azogue et al, 2022;Gensler et al, 2017;Kang, 2018). For instance, Kang (2018) discovered that information attainment and social interaction influenced showrooming and webrooming, while price comparison and assessment seeking only affected showrooming and webrooming, respectively.…”
Section: Showrooming and Webroomingmentioning
confidence: 99%
“…Although there is a general view that the prevalence of cross-channel behavior necessitates companies to integrate retailing mix across channels, it may overlook consumers' differentiated shopping goals that influence their behavior and attitude toward crosschannel consistency. For example, previous research has indicated that the primary goal of showroomers is to get a better deal online (Arora et al, 2022;Gensler et al, 2017). Hence, consumers with high showrooming motivations are unlikely to expect price and promotion consistency across channels but expect greater benefits from the online channel they prefer to shop at (Flavi an et al, 2019).…”
Section: The Moderating Effects Of Showrooming Motivationmentioning
confidence: 99%